2008
DOI: 10.1091/mbc.e07-08-0740
|View full text |Cite
|
Sign up to set email alerts
|

YeastARV1Is Required for Efficient Delivery of an Early GPI Intermediate to the First Mannosyltransferase during GPI Assembly and Controls Lipid Flow from the Endoplasmic Reticulum

Abstract: Glycosylphosphatidylinositol (GPI), covalently attached to many eukaryotic proteins, not only acts as a membrane anchor but is also thought to be a sorting signal for GPI-anchored proteins that are associated with sphingolipid and sterol-enriched domains. GPI anchors contain a core structure conserved among all species. The core structure is synthesized in two topologically distinct stages on the leaflets of the endoplasmic reticulum (ER). Early GPI intermediates are assembled on the cytoplasmic side of the ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
140
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(148 citation statements)
references
References 104 publications
(137 reference statements)
8
140
0
Order By: Relevance
“…arv1 cells harbor defects in sphingolipid and GPI synthesis, and although their overall sterol content is normal, our data, as well as that of others, strongly suggest these lipids are trafficked improperly and thus are mislocalized (Tinkelenberg et al 2000;Swain et al 2002;Fei et al 2008;Kajiwara et al 2008). Membrane microdomains, also known as lipid rafts, are sphingolipidand sterol-rich regions of the plasma membrane, which are capable of mediating membrane sorting, cell adhesion, and signal transduction (Harder et al 1998).…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…arv1 cells harbor defects in sphingolipid and GPI synthesis, and although their overall sterol content is normal, our data, as well as that of others, strongly suggest these lipids are trafficked improperly and thus are mislocalized (Tinkelenberg et al 2000;Swain et al 2002;Fei et al 2008;Kajiwara et al 2008). Membrane microdomains, also known as lipid rafts, are sphingolipidand sterol-rich regions of the plasma membrane, which are capable of mediating membrane sorting, cell adhesion, and signal transduction (Harder et al 1998).…”
Section: Discussionsupporting
confidence: 68%
“…Thus general vesicle-mediated trafficking is only slightly affected in arv1 cells and most likely does not contribute to the mating defects observed. In addition, the kinetics of a-factor internalization in mutant cells is similar to that seen in wild type, indicating that pheromone receptors are localized properly and are functional (Kajiwara et al 2008). Therefore, it is unlikely Ste5 mislocalization results from defects in general protein trafficking.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…For example, in mammals the GPI-GnT complex has been shown to have regulatory contacts with Dpm2, a subunit that also regulates dolichol-phosphate mannose synthase (29). Likewise, in Saccharomyces cerevisiae, subunits of the GPI-GnT complex were shown to physically interact with and regulate Ras signaling (30,31), as well as control intracellular sterol distribution via genetic interactions with ARV1 (32). A large scale split ubiquitin-based protein-protein interaction study also indicated that ScGpi2 in S. cerevisiae interacted with ScGpi19 as well as with ScErg11 and a large number of other proteins involved in many different biochemical pathways of the cell (33).…”
Section: Discussionmentioning
confidence: 99%